Anisotropic Stark effect of carbon monoxide: emergent orbital cooperativity - Jibiao, Li; Xiaosong, Zhu; Emeka, Oguzie (My University, 2019)
Applying external electric fields to molecules gives rise to spectral shifting and splitting, a phenomenon known as the Stark effect. However, a fundamental question of how electronic structures of molecules are modified by electric fields is still not well understood. By applying electric fields to a carbon monoxide molecule, herein we have successfully addressed the fundamental question at orbital scales and discovered that the Stark effect exhibits anisotropic characters depending on the direction of the electric fields with respect to the molecular axis. Based on the fact that applying electric fields along the molecular axis always preserved the orthogonality between the sigma and pi electrons, we found that orbital resemblance-based cooperativity can only operate within either the sigma system in which sigma electrons somehow prefer to resemble each other or the pi electron system in which the 1π electrons experience polarization-based self-resemblance.